2019
DOI: 10.15201/hungeobull.68.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renewable energy on landscape in Europe: Comparison of hydro, wind, solar, bio-, geothermal and infrastructure energy landscapes

Abstract: Landscape quality has become a fundamental issue in the development of renewable energy (henceforth abbreviated RE) projects. Rapid technological advances in RE production and distribution, coupled with changing policy frameworks, bring specific challenges during planning in order to avoid degradation of landscape quality. The current work provides a comprehensive review on RE landscapes and the impacts of RE systems on landscape for most European countries. It is based on a review by an interdisciplinary inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 88 publications
0
23
0
2
Order By: Relevance
“…Thirdly, we review studies based on the socio-spatial approach. Based on the work of Frolova et al [2], we reviewed the literature focusing on solar and wind power that are particularly characterized by conflicts with local communities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, we review studies based on the socio-spatial approach. Based on the work of Frolova et al [2], we reviewed the literature focusing on solar and wind power that are particularly characterized by conflicts with local communities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In rural areas where beautiful landscapes are a local resource, such facilities may disrupt the natural landscape, which may reduce tourism income. Frolova et al [2] indicated that the artificial solar power structures contrasted considerably with the natural landscape. Secondly, if the installation is located on a slope, it is perceived to be a problem.…”
Section: Required Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Frolova [16,17] explored the structural and social processes from which river and hydropower ecosystems have emerged, indicating that the institutional growth of the river landscape in Spain has been closely linked to the growing importance of environmental concerns. Similarly, Frolova, et al [18], investigated the effects of hydropower on the landscape in Europe, concluding that in conjunction with evolving policy structures, rapid technological developments in hydropower development, and distribution face particular challenges during planning to avoid deterioration of landscape quality. Identically, Bohlen and Lewis [19], examined the economic impacts of hydropower dams on property residential values using a geographic information system.…”
Section: Empirical Surveymentioning
confidence: 99%
“…Pasqualetti and Stremke have put forward a framework for the systematic study of energy landscapes-published in a special issue of Energy Research & Social Science entitled 'Spatial Adventures in Energy Studies: Emerging Geographies of Energy Production and Use' [25]. Below, we summarize the three qualifications that were employed in our research and that of other scientists (see, e.g., [32,33]).…”
Section: Characterization Of Energy Landscapesmentioning
confidence: 99%